(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This study examines religious appropriation in English and Uzbek languages through a linguocognitive and linguoculturological lens. By analyzing textual and contextual data, the study highlights how religious terms and concepts are adapted to secular, cultural, and ideological frameworks in both linguistic systems. Results reveal distinctive cognitive mappings and cultural paradigms that influence language use in these two contexts.